Systems pharmacology to decipher the combinational anti-migraine effects of Tianshu formula. (4th November 2015) - Li, Yan; Zhang, Jingxiao; Zhang, Lilei; Chen, Xuetong; Pan, Yanqiu; Chen, Su-Shing; Zhang, Shuwei; Wang, Zhenzhong; Xiao, Wei; Yang, Ling; Wang, Yonghua
Abstract: Migraine is the most common neurovascular disorder that imparts a considerable burden to health care system around the world. However, currently there are still no effective and widely applicable pharmacotherapies for migraine patients. Herbal formulae, characterized as multiple herbs, constituents and targets, have been acknowledged with clinical effects in treating migraine, which attract more and more researchers' attention although their exact molecular mechanisms are still unclear. In this work, a novel systems pharmacology-based method which integrates pharmacokinetic filtering, target fishing and network analysis was developed and exemplified by a probe, i.e. Tianshu formula, a widely clinically used anti-migraine herbal formula in China which comprises of Rhizoma chuanxiong and Gastrodia elata . The results exhibit that 20 active ingredients of Tianshu formula possess favorable pharmacokinetic profiles, which have interactions with 48 migraine-related targets to provide potential synergistic therapeutic effects. Additionally, from systematic analysis, we speculate that R. chuanxiong as the monarch herb mediates the major targets like PTGS2, ESR1, NOS2, HTR1B and NOS3 to regulate the vascular and nervous systems, as well as the inflammation and pain-related pathways to benefit migraine patients. Meanwhile, as an adjuvant herb, G. elata may not only assist the monarch herb to improve the outcome of migraine patients, but also regulate multiple targets like ABAT, HTR1D, ALOX15 and KCND3 to modify migraine accompanying symptoms like vomiting, vertigo and gastrointestinal disorders. Graphical abstract: